Penerapan Etika Bisnis Islam terhadap Perdagangan Sapi di Kecamatan Tanete Riattang Barat Kabupaten Bone - Hasnidar; Haslindah (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2021)
This paper discusses the application of Islamic business ethics, especially in the cattle trade. How is the application of Islamic business ethics to the cattle trade in Tanete Riattang Barat District, Bone Regency. This type of research is a field research using a qualitative descriptive approach. This study uses the methods of observation, interviews, and documentation in collecting the necessary data, the data analysis technique used in this research is descriptive qualitative method. This method is used to reveal facts, circumstances, phenomena, variables and circumstances that occurred during the research and showed the fact. Based on the author's observations, cattle traders have understood Islamic business ethics such as being honest, not taking many oaths and being tolerant in bargaining. Indirectly, cattle traders have understood Islamic business ethics by applying these three principles in conducting the cattle trading business